Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus
(√12 + √8 )(√18 - √27) = ( 2√3 + 2√2 )( 3√2 - 3√3 ) = 6√6 - 6√9 + 6√4 - 6√6 = -18 + 12 = -6

Jawabanmu

2014-03-20T13:32:00+07:00
(√12+√8)(√18-√27)
= √216 - √324 + √144  - √216
= -√324 + √144
= - √81.4 + 12
= -9
4 + 12 atau 12-9√4
2014-03-20T14:21:17+07:00
(√12 + √8 )(√18 - √27)
= (
√12 x √18)(√12 x -√27)(√8 x √18)(√8 x -√27)
= {(
√4 x 3 ) x (√9 x 2 )} {(√4 x 3 ) x -(√9 x 3 )} {(√4 x 2 ) x (√9 x 2 )} {(√4 x 2 ) x -(√9 x 3 )}
= (2
√3 x 3√2) (2√3 x -3√3) (2√2 x 3√2) (2√2 x -3√3)
= 6
√6 - 6√9 + 6√4 - 6√6
= 6√6 (-6.3) + (6.2) - 6√6
= 6√6 - 6√6 - 18 + 12
= 6
semoga bermanfaat :)
-6 hasilnya itu kawan!
iya maaf kurang ngetikya